Long-term Performance of MSWI Bottom Ash in a Test Road Construction - Frogner-Kockum, Paul Christian; Lindqvist, Jan Erik (International Journal of Sustainable Construction Engineering and Technology, 2016)
The study focuses on long-term performances of MSWI bottom ash used as a reinforcement layer in a 8 years old road-construction. Long term properties may change under the combined effects of loading, climate- and chemical conditions. Characterization of the chemical changes in aged MSWI bottom ash is thus of prime interest as secondary alteration is a key process for the ageing of these kind of materials. The MSWI bottom ash in this study comprises a 60 meter-long segment of a test road, which was sampled eight years after construction. The objective of the sampling was to obtain a very low degree of disturbance to the application’s in-situ properties. Access to the sub-base was achieved by removing the surface course and unbound base course, leaving the top surface of the unbound sub-base reachable. Epoxy impregnated slabs were also used for a micro textural and chemical characterization by SEM/EDS of the bottom ash sub-base layer. No cracks that imply movements or rotation of particles in the road construction or other disturbances as due to the sampling process were found. This undisturbed material made it possible to study chemical processes and structural changes that have been ongoing in the test road since it was constructed. The SEM/EDS analysis showed that most particles had reacted to some extent and that reaction-products surrounding aluminum particles were undisturbed. Partly decomposed particles indicate that the reaction (that has been ongoing since the road was constructed) has been slow and incomplete because of the coexistence of metallic aluminum and aluminum hydroxide. It also shows that the material not has been subjected to any physical influence during these 8 years that otherwise would have moved the reaction products from the particles that originally have reacted. Clay mineralization that indicates long-term ageing of the ash material was also detected by XRPD. The pH of the material was lower than 8.5, indicating a mature degree of carbonization. It is also concluded from the study that chemical reactions consistent with this maturity have been taking place in the road construction as indicated by textural relationships.